PENGARUH PROMOSI PENJUALAN DAN CELEBRITY ENDORSER TERHADAP NIAT BELI PRODUK TONY MOLY DELIGHT TINT (STUDI PADA PENGUNJUNG ROYAL PLAZA SURABAYA) - SUKMANING ARUM, WAHYU (Jurnal Ilmu Manajemen (JIM), 2018)
Beautiful is the dream of every woman there are many ways to make yourself look more beautiful by using cosmetics. The potential of the cosmetics industry in Indonesia is promising. Therefore many cosmetic producers want to enter the Indonesian market. Korea is one of the Cosmetic producers that entered the Indonesian market. One of its products is Tony Moly Delight Tint. This study aims to analyze Sales Promotion and Celebrity Endorsers against the intention of buying Tony Moly Delight Tint products. This type of research is a conclusive research with a quantitative approach. The population in this study was visitors to the Royal Plaza Surabaya who wanted to buy special products from Tony Moly Delight Tint. The technique in this study is non probability sampling. The sample used was 220 respondents. Data sender technique in this case is a questionnaire. The data analysis technique uses Multiple Linear Regression with the SPSS 24 program. The results of this study indicate that the variables of Sales Promotion and Celebrity Endorser have a positive effect on Buy Intention. For the next researcher, it is expected to examine the variables outside of this study because the value of Correlation and Coefficient shows a value of 0.567 (R2), meaning that the Purchase Intention varibility can be explained by the variability of Sales Promotion and Celebrity Endorsers by 56.7% while 43.3% are other variables that are not examined in this study. Keywords : celebrity endorser, intention, sales promotion